Pengaruh kompetensi, lingkungan non fisik dan budaya organisasi terhadap kinerja apparat melalui motivasi kerja apparat territorial pada X di Maluku Utara - Sugiono, Edi; Iskandarmanto, Moch (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
Competent human resources with good performance can support organizational success. In this case, this research uses two methods of data analysis, namely descriptive analysis and inferential analysis. In this study, researchers used data collection techniques using questionnaires. The results of this study indicate that competency directly has a positive and significant effect on the work motivation of the Territorial Apparatus. The non-physical work environment directly has a positive and significant effect on the work motivation of the territorial apparatus. Organizational culture directly has a positive and significant effect on the work motivation of the Territorial Apparatus. Competence directly has a positive and significant effect on the performance of the territorial apparatus. The non-physical work environment directly has a positive and significant effect on the performance of the territorial apparatus. Organizational culture directly has a positive and significant effect on the performance of the territorial apparatus. Competence indirectly has a positive and significant effect on the performance of apparatus through work motivation. The non-physical work environment indirectly has a positive and significant effect on the performance of the apparatus through work motivation. Organizational culture indirectly has a positive and significant effect on employee performance through work motivation. Work motivation has a direct and significant positive effect on apparatus performance.